Synthesis of N,N′-bis[(benzo-15-crown-5)-oylmethyl]diaminoglyoxime and its metal complexes - Avciata, U; Demirhan, N; Gül, A (MARCEL DEKKER INC, 1999)
A new macrocyclic ligand (LH2) has been synthesised by the reaction of 4'-omega-aminoacetyl(benzo-15-crown-5) with anti-dichloroglyoxime (EE-diimidoyldichloride-dihydroxyethane). The crystalline complexes of the ligand (LH2) with Cu(II), Ni(II) and Co(II) has also been isolated. Protonation constants of the ligand and overall formation constants have been calculated from potentiometric data using the program TITFIT. Both amino and hydroxyimino groups provide donor atoms together with hydroxyl ions at higher pH values. The order of formation constants of the mononuclear complexes is Cu(II)> U(VI)O-2>Ni(II)> Co(II)> Mn(II).
Keywords: PHOTORESPONSIVE CROWN ETHERS; COBALT(II); COPPER(II); NICKEL(II); URANYL(VI); SALICYLALDIMINE; PALLADIUM(II); CRYSTAL; AMINO; Chemistry